The Inexorable Recoveries of Unemployment - Robert E. Hall; Marianna Kudlyak (Institute of Labor Economics (IZA), 2022)
Unemployment recoveries in the US have been inexorable. Between 1948 and 2019, the annual reduction in the unemployment rate during cyclical recoveries was fairly tightly distributed around 0.1 log points per year. The economy seems to have an irresistible force toward restoring full employment. In the aftermath of a recession, unless another crisis intervenes, unemployment continues to glide down. Occasionally, unemployment rises rapidly during an economic crisis, while most of the time, unemployment declines slowly and smoothly at a near-constant proportional rate. We show that similar properties hold for other measures of the US unemployment rate and for the unemployment rates of many other emerging and advanced countries.
Keywords: E32; J63; J64; 330; business cycle; recovery; unemployment; recession